The fast track to canonical Wnt signaling in MC3T3‐E1 cells protected by substance P against serum deprivation‐induced apoptosis. (27th November 2016) - Yang, Jianguo; Nie, Jiping; Fu, Su; Liu, Song; Wu, Jianqun; Cui, Liang; Zhang, Yongtao; Yu, Bin
Abstract: The canonical Wnt pathway is vital to bone physiology by increasing bone mass through elevated osteoblast survival. Although investigated extensively in stem cells, its role in osteoblastic MC3T3‐E1 cells has not been completely determined. To explore how this pathway is regulated by different conditions, we assessed the anti‐apoptotic effects of substance P on the canonical Wnt pathway in MC3T3‐E1 cells by treating cells with serum deprivation or serum starving with "substance P, " a neuropeptide demonstrated to promote bone growth and stimulate Wnt signaling. The results showed that serum deprivation both induced apoptosis and activated Wnt signal transduction while substance P further stimulated the Wnt pathway via the NK‐1 receptor but protected the cells from apoptotic death. Fast‐tracking of Wnt signaling by substance P was also noted. These results indicate that nutritional deprivation and substance P synergistically activated the canonical Wnt pathway, a finding that helps to reveal the role of Wnt signaling in bone physiology affected by nutritional deprivation and neuropeptide substance P.